Sel Elektrolisis 3–Kompartemen untuk Ekstraksi Magnesium dan Sulfat dari Sistem Larutan MgSO4–KCl–H2O - Rahmanto, Wasino Hadi; Asy’ari, Mukhammad; Rame, Rame; Marihati, Marihati (Jurnal Kimia Sains dan Aplikasi, 2006)
Extraction of magnesium and sulfate from MgSO4–KCl–H2O solution system of 0.1 M salt concentration has been conducted. The 3–compartment electrolytic cell model was designed to fulfill the purpose. The cell is constructed from aquarium plastic box of 417 mL capacity divided into three compartments. Each compartment is separated by fixed plastic wall. One of the compartment with no electrode (mid compartment) was connected either to anodic (left) and cathodic (right) compartment using double filter paper strip of 2 x 6 (in cm) dimension. Electrolysis was performed in atmospheric environment under the 6 volt external electric potential using 7A Montana power supply. Experimental results show that electrolysis systems provide good separation of magnesium and sulfate from solution. Magnesium in the form of Mg(OH)2 and sulfate as H2SO4 has been obtained in about 92 % yield. Clear solution in the mid compartment show the absence of salt residues; both of cationic and anionic species migrate totally toward cathodic and anodic compartment respectively.